2012
DOI: 10.28945/1726
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Understanding of Advanced Properties of Java Exceptions

Abstract: Executive SummaryThis study examines how Information Systems Engineering School students on the verge of their graduation understand the mechanism of exception handling. The main contributions of this paper are as follows: we construct a questionnaire aimed at examining students' level of understanding concerning exceptions; we classify and analyse the students' responses to the questionnaire in order to determine their level of understanding of the mechanism; and we discuss the students' reflections concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In [18], Rashkovits showed that most of college students understand the concept of Java exception handling at the basic level, and the majority of them have difficulty in understanding advanced properties such as use of multiple exceptions, flow of control in the context of exceptions, handling exceptions further up the calling chain, catching and handling hierarchically related exceptions, and overriding methods that throw exceptions. They also provided a tutorial of exception handling, and quoted that exception handling is perceived as a relatively difficult task by novice programmers.…”
Section: Related Workmentioning
confidence: 99%
“…In [18], Rashkovits showed that most of college students understand the concept of Java exception handling at the basic level, and the majority of them have difficulty in understanding advanced properties such as use of multiple exceptions, flow of control in the context of exceptions, handling exceptions further up the calling chain, catching and handling hierarchically related exceptions, and overriding methods that throw exceptions. They also provided a tutorial of exception handling, and quoted that exception handling is perceived as a relatively difficult task by novice programmers.…”
Section: Related Workmentioning
confidence: 99%